The study of lactate/albumin ratio as a predictor of in-hospital mortality in patients with sepsis and septic shock in a tertiary care hospital - H A Krishnamurthy; U Kishor (Wolters Kluwer Medknow Publications, 2024)
Background: Sepsis is a common and deadly disease that is characterized by elevated levels of acute phase reactants such as high-sensitivity C-reactive protein, lactate dehydrogenase, ferritin, procalcitonin, interleukin (IL-6), tumor necrosis factor, and IL-1. These markers are often used for early diagnosis, management, and risk stratification in patients with septic shock, but they may not be accessible in resource-poor settings with financial constraints. This study aimed to investigate the potential use of the ratio between serum lactate and negative acute phase reactant serum albumin level as a prognostic marker for the outcome of sepsis in resource-poor and -constrained settings. Materials and Methods: The study was a prospective observational study that included 122 patients admitted to the intensive care unit and emergency ward with sepsis or septic shock. Ethical clearance was obtained from the Ethics Committee of Mysore Medical College and Research Institute, and informed consent was obtained from the patients and their attendants. Blood samples for analysis of arterial blood gases, albumin, and other biochemical parameters were collected on the 1st and 3rd days of admission. The outcome of the disease was compared to these parameters using statistical methods such as ANOVA and Chi-square tests with multivariate analysis. Results: The study population consisted of 54.09% males, with one-third of the patients belonging to the age group of 61-70 years. The mortality rate was 27%. The mean serum lactate level on day 1 was 1.7 ± 0.15 mmol/L and on day 3 was 2.65 ± 0.32 mmol/L. The mean serum albumin level on day 1 was 3.14 ± 0.14 g/dL and on day 3 was 3.03 ± 0.13 g/dL. The lactate/albumin ratio on day 1 was 0.49 ± 0.12 and on day 3 was 0.89 ± 0.1 and was positively correlated with the severity of sepsis and septic shock (P < 0.001) and showed a greater significance than lactate or albumin alone. Conclusion: The serum lactate/albumin ratio is a highly sensitive marker that is noninferior to other high-cost biomarkers in assessing the daily prognosis of patients with sepsis in resource-poor and -constrained settings. This study suggests that the lactate/albumin ratio may be a cost-effective, novel, easily feasible, and relevant investigation for assessing the severity and mortality of sepsis and septic shock in rural resource-limited and financially poor hospital settings.